2016
DOI: 10.1155/2016/2631625
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity and Inducible Nitric Oxide Synthase Activation by RuNO Complex

Abstract: Parasites of the genus Leishmania are capable of inhibiting effector functions of macrophages. These parasites have developed the adaptive ability to escape host defenses; for example, they inactivate the NF-κB complex and suppress iNOS expression in infected macrophages, which are responsible for the production of the major antileishmanial substance nitric oxide (NO), favoring then its replication and successful infection. Metal complexes with NO have been studied as potential compounds for the treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…They change the immunological and inflammatory host responses to their profit by suppressing the nuclear factor κ B (NF κ B) complex. The latter leads to the downregulation of nitric oxide synthase (iNOS) expression in infected macrophages and hinder the production of nitric oxide (NO), assisting its replication and sustained infection (Marcusso Orsini et al ., 2016). In recent years, many studies have been carried out to explore the possibility of development of new drugs with immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…They change the immunological and inflammatory host responses to their profit by suppressing the nuclear factor κ B (NF κ B) complex. The latter leads to the downregulation of nitric oxide synthase (iNOS) expression in infected macrophages and hinder the production of nitric oxide (NO), assisting its replication and sustained infection (Marcusso Orsini et al ., 2016). In recent years, many studies have been carried out to explore the possibility of development of new drugs with immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the leishmanicidal potential of the ruthenium nitrosol complex (RuNO, S8) against L. brasiliensis by means of an in vitro (mice dermal fibroblasts) and an in vivo study (using hamsters) [41] . The nitrosyl ruthenium complexes have proven biological activity, such as antiparasitic, antiangiogenic, analgesic, gastroprotective and cerebral neuroprotection [44–49] . In this study, the authors showed that RuNo had no cytotoxic effect on dermal fibroblasts at any of the concentrations tested.…”
Section: New Molecules With Potential For Treatmentmentioning
confidence: 95%
“…Despite good leishmanicidal action, this study did not report any possible mechanism of action, however, the authors discuss that NO is one of the crucial molecules in the control of the parasitic load during the development of cutaneous leishmaniasis. Ruthenium complexes have shown to function as NO donor and associated with antileishmanial activity by NO release and intracellular elimination of the parasite [44,50] …”
Section: New Molecules With Potential For Treatmentmentioning
confidence: 99%
“…Those efforts resulted in promising compounds such as NAMI-A, KP1019, RAPTA-C and others, which were able to cause cell death through mechanisms distinct from platinum drugs. [21][22][23] Moreover, in the following years, several Ru-based species were synthesized exhibiting diverse therapeutic activities as antitumoral, 24,25 bactericide, [26][27][28] anti-parasitic, [29][30][31] and antiinflammatory [32][33][34] agents, revealing great potential for pharmacological application.…”
Section: Introductionmentioning
confidence: 99%